Kepemimpinan Kepala Sekolah Dalam Meningkatkan Kinerja Guru - Djunaidi Djunaidi (Sekolah Tinggi Ilmu Tarbiyah Ibnu Sina Malang, 2018)
Education is the most strategic way to enhance the quality of human resources. The improvement of education is also determined by principals leadership. As a part of the management function, leadership also determine the goal achievement. Successful principals leadership activity is affected many factors, including the good relationship between staff and leader, leader background, maturity and latitude in social relationship, and human attitudes. Thus, effective school leader is who competent to be the role model of their subordinate. Beside that, principals must be understood with four leadership styles: authoritarian; pseudo-democratic; laizes faire (freestyle) and democratic. Principals need to have competencies: flexibility, change implementation, interpersonal understanding, empowering, team facilitation, dan portability.